A Rare Case of Fetal Hydrothorax Treated through Amniocentesis and Thoracentesis - Albu, Dinu-Florin; Albu, Cristina-Crenguta; Albu, Stefan-Dimitrie; Dumitrescu, Mihai (International Journal of Medical Research and Review, 2015)
We present the rare case of a 27-year-old Caucasian female which was admitted in our service at 27 weeks of gestation after beig discovered with left fetal hydrothorax during routine prenatal ultrasound. Samples of maternal blood and amniotic fluid (trough amniocentesis) were obtained in order to establish the cause (immune or non-immune) and fetal thoracentesis was performed in order to allow for lung re-expansion. Analysis of the amniotic and pleural fluids trough QF-PCR and amniocyte cultures established the diagnosis of Down syndrome and the decision was taken to perform cesarean section at 33 weeks of gestation following two weeks treatment with dexamethasone.